Depletion of dopamine in Parkinson's disease and relevant therapeutic options: A review of the literature - Ramesh, Sairam; Arachchige, Arosh S. Perera Molligoda (AIMS neuroscience, 2023)
Parkinson's disease (PD) is a progressive neurodegenerative disorder that affects motor and cognition functions. The etiology of Parkinson's disease remains largely unknown, but genetic and environmental factors are believed to play a role. The neurotransmitter dopamine is implicated in regulating movement, motivation, memory, and other physiological processes. In individuals with Parkinson's disease, the loss of dopaminergic neurons leads to a reduction in dopamine levels, which causes motor impairment and may also contribute to the cognitive deficits observed in some patients. Therefore, it is important to understand the pathophysiology that leads to the loss of dopaminergic neurons, along with reliable biomarkers that may help distinguish PD from other conditions, monitor its progression, or indicate a positive response to a therapeutic intervention. Important advances in the treatment, etiology, and pathogenesis of Parkinson's disease have been made in the past 50 years. Therefore, this review tries to explain the different possible mechanisms behind the depletion of dopamine in PD patients such as alpha-synuclein abnormalities, mitochondrial dysfunction, and 3,4-dihydroxyphenylacetaldehyde (DOPAL) toxicity, along with the current therapies we have and the ones that are in development. The clinical aspect of Parkinson's disease such as the manifestation of both motor and non-motor symptoms, and the differential diagnosis with similar neurodegenerative disease are also discussed.